The Phenomenon of Disruption in Human Resource Management: A Systematic Literature Review - Purnomo, Hery; Samari; Faisol Hambali (HM Publisher, 2023)
Disruptions in human resource management (HRM) include changes in the way companies recruit, manage, retain, and develop their employees. In the ever-evolving digital era, technologies such as artificial intelligence, data analytics, and automation have become key drivers of this change. In addition, shifts in employee preferences and expectations also affect HRM practices. This study aimed to conduct a systematic review to explore the phenomenon of disruption in human resource management. The literature search process was carried out on various databases (PubMed, Web of Sciences, and Google Scholar) regarding the analysis of the disruption phenomenon in human resources management. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Disruption in human resource management is a necessity. The phenomenon of disruption has changed aspects of human resource management related to the use of technology, digitalization of human resource management services, orientation towards employee satisfaction, and the adoption of a collaborative and inclusive culture in organizational leadership.